PENGAWASAN DINAS PETERNAKAN DAN PERIKANAN TERHADAP IZIN USAHA PEREDARAN PAKAN DI KABUPATEN BLITAR: PENGAWASAN DINAS PETERNAKAN DAN PERIKANAN TERHADAP IZIN USAHA PEREDARAN PAKAN DI KABUPATEN BLITAR - makromi, hernanda sukron; WIDODO, HANANTO (Universitas Negeri Surabaya, 2018)
Quality and safety are efforts to control risk factors for contamination of feed, so that it is safe for consumption. Feed management carried out by feed entrepreneurs must meet the quality and safety of feed. The obligations of feed business actors are regulated in the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 22/PERMENTAN/PK.110/6/2017 concerning Registration and Distribution of Feed. In fact, there are still feed business actors in Blitar Regency, especially Ponggok District who do not meet the quality and safety of feed. This study aims to determine the form of supervision carried out by the Livestock and Fisheries Service of Blitar Regency in supervising feed business actors related to quality and safety and the obstacles experienced by the Department of Animal Husbandry and Fisheries of Blitar Regency. This research includes sociological juridical research. The data source that is used is primary data and secondary data. Data was collected by means of interviews and documentation which were then analyzed using qualitative analysis methods. The results showed that the form of preventive supervision in the form of socialization and repressive supervision in the form of giving verbal warning sanctions carried out by the Department of Animal Husbandry and Fisheries of Blitar Regency. The obstacles experienced by the Livestock and Fisheries Service of Blitar Regency are the lack of supervisory staff and the lack of knowledge and understanding of feed business actors regarding their obligations to meet feed quality and safety.